The Application of the MFN Principle into 'the Over Top Companies' in Investment Activities of Indonesia - Ansory, Wachid Aditya; Widiyanti, Ikarini Dani; Kumala Sari, Nuzulia (University of Jember, 2019)
The Most-Favored-Nation (MFN) principle is one of international consensuses, especially for countries registered as members of the World Trade Organization (WTO). The principle is related to investment and international trade within the framework of economic liberalization. At its core, the MFN principle ensures equitable treatment of all parties economically active within a country. Recently, in Indonesia, the Over Top company conducted business activities without paying taxes to the government. The case of the Over Top company highlights an unfair business situation in Indonesia, enabled by the Indonesian government through a poorly established monitoring system and codification of laws. This study argues that the absence of taxation, regulation, and fraud laws for the Over Top Companies in Indonesia, and the Indonesian government is responsible for the enforcement and maintenance of tax laws and the MFN principle for all entities conducting business in the state. Keywords: MFN Principle, Over Top Companies, Investment in Indonesia.